SEBARAN CURAH HUJAN SAAT KEJADIAN BANJIR JANUARI 2021 DI DAS BARITO WILAYAH KALIMANTAN SELATAN - Cahyaningsih, Putri; Kissinger, Kissinger; Kadir, Syarifuddin; Fatmawati, Fatmawati (EnviroScienteae, 2024)
South Kalimantan Province experienced one of the largest floods in recent years in January 2021, resulting in extensive and significant impacts on society and the environment. The purpose of this study is to analyze the spatial distribution of rainfall and the impact of flooding in the Barito River Basin, South Kalimantan, in January 2021. The research area covers the Barito River Basin from Tabalong Regency to Banjarmasin City. The study uses rainfall data from Automatic Rain Gauges (ARG), radar data, and flood reports from the Regional Disaster Management Agency (BPBD), the Meteorology, Climatology, and Geophysics Agency (BMKG), and the River Basin Authority (BWS). Data analysis is conducted using interpolation techniques and Geographic Information Systems (GIS) mapping to determine the distribution of rainfall and flooding. The results show a similarity in patterns between rainfall distribution and flood-affected areas. Given that rainfall is a factor beyond our control in flooding, effective flood management and early warning systems are crucial in flood-prone areas.